A global comparative field study to evaluate the factor VIII activity of efanesoctocog alfa by one‐stage clotting and chromogenic substrate assays at clinical haemostasis laboratories - Pipe, Steven; Sadeghi‐Khomami, Ali; Konkle, Barbara A.; Kitchen, Steve; Negrier, Claude; Liu, Mingjie; Santagostino, Elena; Willemze, Annemieke; Abad‐Franch, Lydia; Knobe, Karin; Seth Chhabra, Ekta (Haemophilia : the official journal of the World Federation of Hemophilia, 2024)
Introduction Structural and chemical modifications of factor VIII (FVIII) products may influence their behaviour in FVIII activity assays. Hence, it is important to assess the performance of FVIII products in these assays. Efanesoctocog alfa is a new class of FVIII replacement therapy designed to provide both high sustained factor activity levels and prolonged plasma half‐life. Aim Evaluate the accuracy of measuring efanesoctocog alfa FVIII activity in one‐stage clotting assays (OSAs) and chromogenic substrate assays (CSAs). Methods Human plasma with no detectable FVIII activity was spiked with efanesoctocog alfa or a full‐length recombinant FVIII product comparator, octocog alfa, at nominal concentrations of 0.80 IU/mL, 0.20 IU/mL, or 0.05 IU/mL, based on labelled potency. Clinical haemostasis laboratories (N = 35) tested blinded samples using in‐house assays. Data from 51 OSAs (14 activated partial thromboplastin time [aPTT] reagents) and 42 CSAs (eight kits) were analyzed. Results Efanesoctocog alfa activity was reliably (±25% of nominal activity) measured across all concentrations using OSAs with Actin FSL and multiple other aPTT reagents. Under‐ and overestimation of FVIII activity occurred with some reagents. No specific trend was observed for any class of aPTT activators. A two‐ to three‐fold overestimation was consistently observed using CSAs and the OSA with Actin FS as the aPTT reagent across evaluated concentrations. Conclusion Under‐ or overestimation occurred with some specific OSAs and most CSAs, which has been previously observed with other modified FVIII replacement products. Efanesoctocog alfa FVIII activity was measured with acceptable accuracy and reliability using several OSA methods and commercial plasma standards.